PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN, FAKTOR SOSIAL, DAN KONDISI YANG MEMFASILITASI TERHADAP MINAT PENGGUNAAN E-FILING - Syaninditha, Sang Ayu Putu; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
E-filing is the modernization of the tax administration system in Indonesia to facilitate taxpayers in submitting his notice electronically conducted through an online system in real time. This study aims to determine effect the perception of usefulness, perceived ease, social factors and conditions that facilitate the interest of the behavior of individual taxpayers in the use e-filing by applying the model of the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). This research was conducted at the Tax Office (KPP) Pratama Gianyar. This study uses Slovin formula for determining the total sample of 100 individual taxpayers with accidental sampling method. Data collected through questionnaires. The analysis technique used is multiple linear regression. The results showed that perceptions of usefulness, perceived ease, social factors and conditions that facilitate joint significant positive effect on interest the behavior of individual taxpayers in the use of e-filing.
Keywords: Perception of Usefulness, Perceived Ease, Social Factors, Conditions that Facilitate, E-Filing